Transcranial direct current stimulation in sports training: Potential approaches - Banissy, M. J.; Muggleton, N. G. (Frontiers in Human Neuroscience, 2013)
Successful sporting performance is a result of sustained excellence in a number of factors. Some of these, such as high levels of physical fitness, are common to most sports but it is also true that a large number of sports require excellent levels of motor coordination and less well-defined factors such as "the will to win." While these factors are most likely to spring to mind when considering excellent sporting performance, a range of other abilities may also contribute to success depending on the nature of the sport. These include visual detection (e.g., when a fast moving object such as a cricket ball must be judged or hit) and anticipation (e.g., in situations where the ability to predict or infer the behavior of an opponent may be beneficial). For example, tennis players show a range of enhanced abilities compared to less skilled players related to anticipation in short time windows, such as extracting information from posture (Rowe and McKenna, 2001) or use of more efficient visual search behaviors. Recently it has also been shown that tennis players show better temporal preparation compared to fitness-matched controls (Wang et al., 2013a) as well as showing altered patterns of inhibitory control (Wang et al., 2013b), implying that they may be better able to modulate their behavior.